EFEKTIFITAS TEKNIK PAPER SEMINAR UNTUK MENGAJAR MENULIS DITINJAU DARI AKTUALISASI DIRI MAHASISWA - Arri Kurniawan; Sri Lestari; Reni Martha (Jurnal Penelitian LPPM (Lembaga Penelitian dan Pengabdian kepada Masyarakat) IKIP PGRI MADIUN, 2015)
Orientation: Using technique in teaching is used to improve students' cerativity and ability in writing that help students in process of prewriting, writing, editing phase, revising, and evaluatin. Researcher tried to campare in using teaching technique based on students' self-actualization. Research purpose: This research is aimed at finding out whether: (1) Paper Seminar technique is moreeffective than Peer Editing Technique to teach writing skill; (2) the students having high selfactualization have better writing skill than those having low self-actualization; and (3) there is an interaction between teaching techniques and students' self-actualization in teaching writing to the third semester students of English Department, IKIP PGRI Madiun in the academic year of 2013/2014.Research design: The research method was an experimental study. The researcher used cluster random sampling to get the sample. There were two classes used as sample. One class consisted of 30 students who were experimental class taught by Paper Seminar technique and the other 30 students were as control class taught by Peer Editing technique. The instruments of collecting data are writing test and questionnaire. The data were analyzed by using multifactor analysis of variance 2x2. Then, it was analyzed by using Tukey test. Main Finding: The research findings show that: (1) Paper Seminartechnique is more effective than Peer Editing technique; (2) The students having high selfactualization have better writing skill than those having low self-actualization; and (3) There is an interaction between teaching techniques and students' self-actualization in teaching writing. Based on the research findings, in general it can be concluded that Paper Seminar technique is an effectivetechnique to teach writing. Therefore, the teacher is suggested to apply Paper Seminar technique for teaching writing.